2018
DOI: 10.1111/mec.14475
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of thermal adaptation and evolutionary potential of conspecific populations to changing environments

Abstract: Heterogeneous and ever-changing thermal environments drive the evolution of populations and species, especially when extreme conditions increase selection pressure for traits influencing fitness. However, projections of biological diversity under scenarios of climate change rarely consider evolutionary adaptive potential of natural species. In this study, we tested for mechanistic evidence of evolutionary thermal adaptation among ecologically divergent redband trout populations (Oncorhynchus mykiss gairdneri) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 77 publications
8
93
0
Order By: Relevance
“…The minimal overlap and difference in numbers of SNPs identified between F ST outlier approaches identified may indicate different sensitivities of each approach to the effects of genetic drift and structure. Notably, studies comparing outflank and bayescan have found little overlap between the approaches (e.g., Bernatchez, Laporte, Perrier, Sirois, & Bernatchez, ; Chen, Farrell, Matala, & Narum, ; Micheletti, Matala, Matala, & Narum, ). The significant SNP associations using EAA were unique to each environmental variable in 41%–79% of cases (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The minimal overlap and difference in numbers of SNPs identified between F ST outlier approaches identified may indicate different sensitivities of each approach to the effects of genetic drift and structure. Notably, studies comparing outflank and bayescan have found little overlap between the approaches (e.g., Bernatchez, Laporte, Perrier, Sirois, & Bernatchez, ; Chen, Farrell, Matala, & Narum, ; Micheletti, Matala, Matala, & Narum, ). The significant SNP associations using EAA were unique to each environmental variable in 41%–79% of cases (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to interspecific differences in thermal tolerance, however, intraspecific differences appear to be relatively small (Chen et al. ) and less malleable over short time spans, so more plastic phenotypic traits may offer better opportunities for manipulation (Crozier et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these possible limitations, our results demonstrate multilocus associations with variation in both upper thermal tolerance and hypoxia tolerance, indicating that relatively high proportions of phenotypic variation in CT max and LOE hyp can be attributed to combinations of SNP variation across multiple loci (approximately 47 and 35 SNPs, respectively). Polygenic bases for phenotypic variation have been demonstrated for several ecologically relevant traits (Brieuc et al, ; Holliday et al, ; Laporte et al, ; Nemri et al, ), and recent studies in rainbow trout and corals also detected a polygenic basis for variation in thermal tolerance (Chen, Farrell, Matala, & Narum, ; Rose et al, ). Together these results highlight the importance of incorporating models of adaptive responses based on many loci of small effect into forecasts of the organismal responses to climate change (Bay et al, ; Pritchard & Di Rienzo, ).…”
Section: Discussionmentioning
confidence: 99%